Odpowiedź:
a) (2a-3b+1)-(3a+2b-4)-(a-6b+2)= 2a-3b+1-3a-2b+4-a+6b-2= 6b+3-4a= 6×(-5)+3-4×(-3)= -30+3+12= -15
b) -(3a-2b-3c)+(5a-4b+4c)-(a-5b-c)= -3a+2b+3c+5a-4b+4c-a+5b+c= a+3b+8c= -6+3×3+8×(-1)= -6+9-8= -5
c) (2x²+3x-5)-(3x²-5x+8)= 2x^2+3x-5-3x^2+5x-8= -x^2+8x-13= 3^2+8×3-13= 9+24-13= 20
d) -(3-2x+4x²)+(1-3x-6x²)= -3+2x+4x^2+1-3x-6x^2= -2-x-2x^2= -2-(-3)-2×(-3)^2= -2+3-2×9= -5-18= -23
e) -(2x-x²)-[2-3x-(2x²-3x+4)]= -2x+x^2-[2-3x-2x^2+3x-4]= -2x+x^2-2+3x+2x^2-3x+4= -2x+3x^2+2= -2×(-1/2)+3×(-1/2)^2+2= 1+3×1/4+2= 3 3/4 (trzy i trzy-czwarte)
f) 3-[-(2x-3x²)+(1-3x+x²)]+4x²= 3-[-2x+3x^2+1-3x+x^2]+4x^2= 3+2x-3x^2-1+3x-x^2+4x^2= 2+5x= 2+5×(-0,3)= 2-1,5= 0,5
[Mogą pojawić się błędy rachunkowe!]
Szczegółowe wyjaśnienie: